THE ROLE OF THE FINANCIAL MARKET IN ATTRACTING INVESTMENT (E Global Congress, 2025)
The evolution of world business shows that capitalist movements have accelerated in economic trends over the years. As a result, the concepts of investment, diversification, shares, dividends have entered the business environment. A business culture is one in which there is mutual mobilization of equity, in which there are many rules of the game, expected risks, and market competition. If we look at the economic performance of developed countries, it falls at the expense of large companies. We may have a question, how can 4/1 of the world belong to big companies. The answer is simple, in the proper management of business culture, in the worldview. In business, the most important thing is not always to make a profit, but also to fight for the company’s own brand. Today, modern marketing methods are widely used to enter the market, which serves as a mechanism for business development and finding a position in the market. In the analysis of our article, you will see that the annual capitalization of the largest companies is very high, even much higher than the GDP of some developing countries. This, in turn, has a positive impact on the social health of the country.